PRINCIPLES OF EFFECTIVE ORGANIZATION OF ARTISTIC-AESTHETIC TASTE OF PRIMARY CLASS STUDENTS THROUGH MUSIC (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article describes the forms of effective organization of artistic and aesthetic taste of elementary school students through musical means.